Islam and the Pan-Abrahamic Problem - Sijuwade, Joshua R. (Religions, 2025)
This article aims to formulate a philosophical problem that is grounded upon the Pan-Abrahamic nature of early Islam, focusing on the implications that this has for understanding the identity of the contemporary Islamic community. This philosophical problem—termed the Pan-Abrahamic Problem—is structured around the examination of Prophet Muhammad’s leadership and the inclusivity of the early Islamic community, as proposed by Fred Donner in the form of the Pan-Abrahamic Thesis. The formulation of this philosophical problem is presented through the lens of the philosophical criteria of continuity and connectedness of aims (doctrine) and organisation, as proposed by Richard Swinburne. This philosophical problem will, thus, offer a challenge against traditional exclusivist narratives within Islam, ultimately aiming to emphasise the inclusive and pluralistic foundation of the religion and the significance of this for the contemporary Islamic identity.